Seroprevalence of Powassan Virus Infection in an Area Experiencing a Cluster of Disease Cases: Sussex County, New Jersey, 2019. (17th January 2022) - Vahey, Grace M; Wilson, Nicolette; McDonald, Emily; Fitzpatrick, Kelly; Lehman, Jennifer; Clark, Sandhya; Lindell, Kristine; Pastula, Daniel M; Perez, Stephen; Rhodes, Heather; Gould, Carolyn V; Staples, J Erin; et al.
Abstract: In 2019, a geographically focal cluster of 3 Powassan virus neuroinvasive disease cases occurred in New Jersey. We conducted a serosurvey of 273 adult area residents and estimated that immunoglobulin M seroprevalence was 0.31% (95% confidence interval [CI], .04%–1.00%) and 23% (95% CI, 7%–100%) of infections result in neuroinvasive disease. Abstract : A serosurvey of 273 residents of a New Jersey community with several recent Powassan virus neuroinvasive disease cases estimated IgM seroprevalence at <1% and that roughly one-quarter of infections result in neuroinvasive disease.